Penyuluhan Literasi Membaca Dan Menulis Siswa SMPN 4 Subang Melalui Implementasi Kegiatan Kreatif Berbasis Bahasa Dan Sastra Indonesia - Kurnia Wahyu Kinaya; Rahayu Fitriani; Razwa Nabila; Ririn Khaerunisa; Irpan Maulana (Pusmedia Group Indonesia, 2026)
Reading and writing literacy are fundamental to academic success; however, students' literacy skills in Indonesia remain relatively low. This community service program aimed to enhance the reading and writing literacy interest and skills of Grade IX-A students at SMP Negeri 4 Subang through an interactive Indonesian language and literature approach. The program implementation combined awareness-raising and capacity-building strategies, which were carried out in three stages: conceptual socialization, two-way discussions, and creative practice activities. The program was evaluated through participant observation and reflection on students' written work. The results demonstrated that the interactive approach effectively increased student participation and reduced resistance to reading and writing activities. Although students initially experienced limited vocabulary when composing poetry, the guidance provided enabled all 27 participants to complete their work independently. Overall, the program successfully enhanced students' motivation, improved their understanding of literature, and fostered the development of a more positive and sustainable literacy culture within the school environment.